Importance of scientific research for Achieving Sustainable Development Goals during Covid19 Pandemic: Northern Technical University - A Case Study - Alyaa Abbas AL-Attar; Omar Rafae Alomar; Mohammed Khalid Yousif (Journal of Sustainability Perspectives, 2022)
Scientific progress in any country is measured by the importance that is given to scientific research. Recently, the interest in scientific research has increased by the local and international universities in various fields of sciences, given its importance in achieving sustainable development goals, where several countries and universities have initiated to increase scientific research funds. Moreover, the reputation of scientific research in the universities strongly depends on the quality and quantity of papers that are published in the international journals. Thus, the main goal of this study is to investigate and identify the reality of the scientific research situation at Northern Technical University during Covid19 Pandemic (i.e., from 2020 till now). This study is based on the descriptive approach and method of analysis for the published papers that related to the sustainable development topics, which is adopted by UI GreenMetric ranking. The data of the published papers have been collected from the Google Scholar website using the same methodology that was approved in the UI GreenMetric ranking. Those publications have been classified based on the keywords, university researchers and the affiliation of the university’s colleges and institutes. The present data has been compared with data of previous years. Keyword: UI Green metric, sustainability, renewable energy, environment